Removal of methylene blue from aqueous solutions by adsorption on amorphous silicon dioxide from rice husks - O. D. Arefieva (IWA Publishing, 2021)
This study shows the effect of conditions on methylene blue sorption from aqueous solutions using amorphous silicon dioxide obtained from rice husk by oxidative roasting with and without pre-treatment with 0.1 M HCl. Adsorption activity for methylene blue increases with increasing pH, reaching its maximum above the point of zero charge. Thermodynamic parameter values (ΔG298 > 0, ΔH < 0, ΔS > 0) indicate that methylene blue adsorption is exothermic and occurs with an increase in molecular mobility in the adsorption layer. The process is described by the Freundlich and Dubinin-Astakhov equations, which indicates that it is determined by both electrostatic interaction with active centers on the surface and the volumetric filling of micropores. Highlights Characterization of the rice husk ash with different silica contents.; The study of the effect of conditions on the sorption of methylene blue from aqueous solutions.; The mechanism of adsorption of methylene blue by silicon-containing sorbents from rice husk.;